Different types of bowing technique for violin in the baroque and romantic eras / Izzat Syazwan Ab Halim - Ab Halim, Izzat Syazwan (2013)
The musician makes a string vibrate by drawing the bow across it with the right hand. The speed and pressure of the bow stroke control the dynamics and tone colour of the sound produced. By pressing a sting against the fingerboard, the player varies the length of its vibrating portion and so changes its pitch (Askenfelt, 1995). String instruments need a bow to produce a sound, without a how, a string instruments such as violin, viola, cello and double bass can't produce a sound except a pizzicato sound. So in order to play string instruments, each of file string instruments player need to have a how. The sound production is produce when the bow stroke the string, the string will vibrate and send the vibration to the sound post and the vibration will produce the sound. First of all, western music, for the Last one thousand years, has been marked by almost constant stylistic change. Expressively constructively, and instrumentally different musical style minor the vastly different historical environments in which they were created (Greenberg, 2011, p7-8). Bow is one of the thing that affected by the changes of the music revolution. Bow consists of a special shaped stick with other material forming a ribbon stretched between its ends which is used to stoke the string and create the sound. Different musical cultures or different era have shape and adopt various design for the bow. For example, in some how a single cord is stretched between the ends of the stick. For western country the tradition of a bow maker, bow for the instruments for the violin and strings family the bank of horsehair is normally employed but sometimes for the middle class bow a synthetic hair is used to replace the horsehair (Askenfelt, 1995). The manufacture of the bow is considered a demanding craft and a well made bow which is a good bows command high prices. For the bow maker, skill to choose high quality of flu: bow stick is very important in order to make sure that the bow is in good condition and balance from the frog to tip. Historically, western bow have been made from pernambuco wood from brazil. However, pernambuco is now an endangered species which people export it regularly by international treaty. So the maker try to develop a new bow from the synthetic material include carbon fibre epoxy composite and fibre glass. Carbon fibre bows have become very popular, and some of the better carbon fibre bows are now comparable to fine pernambuco sticks. For every century. Every instruments or how have involved or develop into a good condition So for Baroque era the bow will be different from classical and romantic era because of the development of the instruments m the how that we use today. Every performer will call bow is the soul of the violin because it is be used by the performer to produce various tonal colours on the violin. This research will focusing on the importance of the bow stick on how it is used for producing sound through the types of bowing technique (stroke) on the violin in the era of Baroque and Romantic.